2013
DOI: 10.1509/jmr.10.0072
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Customer–Firm Relationships: How Attachment Styles Help Explain Customers' Preferences for Closeness, Repurchase Intentions, and Changes in Relationship Breadth

Abstract: Many firms strive to create relationships with customers, but not all customers are motivated to build close commercial relationships. This article introduces a theoretical framework that explains how relationship-specific attachment styles account for customers' distinct preferences for closeness and how both attachment styles and preferences for closeness influence loyalty. The authors test their predictions with survey data from 1199 insurance customers and three years of purchase records for 975 of these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
204
3
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(224 citation statements)
references
References 69 publications
(78 reference statements)
10
204
3
7
Order By: Relevance
“…As anticipated, anxious attachment style related negatively with satisfaction with their bank (b= -.15, p<01), not being loyal to their bank (b= -.14, p<.01) and identification with the bank (b= -.11, p<.01), (Table 1). Our findings are consistent with findings in Mende et al (2013). Avoidant attachment was not related significantly with satisfaction, loyalty, or identification.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…As anticipated, anxious attachment style related negatively with satisfaction with their bank (b= -.15, p<01), not being loyal to their bank (b= -.14, p<.01) and identification with the bank (b= -.11, p<.01), (Table 1). Our findings are consistent with findings in Mende et al (2013). Avoidant attachment was not related significantly with satisfaction, loyalty, or identification.…”
Section: Resultssupporting
confidence: 92%
“…Two studies in the literature thus far are noteworthy. First, Mende et al (2013) found that attachment styles measured with a domain-specific firm attachment scale affected consumers' degree of satisfaction with the firm's services: avoidant and anxious attachment styles correlated r= -.50 and r= -.31, respectively, with customer satisfaction (defined as satisfied, content, and happy with the service). Another article on service satisfaction of consumers (Mende & Bolton, 2011) found similar negative correlations between avoidant and anxious attachment styles and customer satisfaction, r= -.34 and r= -.58, respectively.…”
Section: Study 1: the Relationship Between Attachment Styles And Satimentioning
confidence: 99%
See 1 more Smart Citation
“…However, this approach is increasingly accepted in the academic literature and is appropriate under certain conditions (Fuchs & Diamantopoulos, 2009;Hoeppner, Kelly, Urbanoski, & Slaymaker, 2011;Mende, Bolton, & Bitner, 2013). Moreover, single-item measures are likely to be more appropriate for experiments situated in organisations, given the individuals'/employees' willingness, time restrictions or lack of appropriate incentives to motivate filling in extensive questionnaires (Biner & Kidd, 1994;Deutskens, De Ruyter, Wetzels & Oosterveld, 2004).…”
Section: Measures Reliability and Data Analysismentioning
confidence: 99%
“…In his seminal work, Hofstede (1980) identified what he called national culture to belong to four categories, namely individualism/collectivism, power distance, uncertainty avoidance and masculinity/femininity (Gelfand, Leslie, & Fehr, 2008;Hui, Ho, & Wan, 2011;Lai, He, & Zhou, 2013;Mende, Bolton, & Bitner, 2013). Later in 1991, Hofstede introduced the fifth category of culture, long-term orientation (Fang, 2003).…”
Section: Possible Moderation Effect Of Long-term Orientationmentioning
confidence: 99%